Does country level sustainability reporting affect sustainable development of a country? Evidence from developed and developing countries - Allah Ditta; Zeeshan Mahmood (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The role of accounting and reporting in sustainable development has been gaining prominence over the last few decades. There is advocacy by the sustainability network associations (especially Global Reporting Initiative) that corporate sustainability reporting enables the sustainable development of a country. This study aims to find an empirical connection between corporate sustainability reporting of the country and the sustainable development of the country. A 6-year data set, ranging from 2014 to 2019 relevant to sustainability reporting and sustainable development, was used to test the hypothesis by controlling the effect of countries' governance index and countries' global competitive index. E-views-9 software was used for data analysis. Panel regression techniques were applied to find out a relationship between sustainability reporting and sustainable development. Empirical results revealed that there is a positive and significant relationship between sustainability reporting of the country and sustainable development of the country. Results also showed that the impact of country-level sustainability reporting on sustainable development is stronger in developed countries as compared to developing countries. This paper contributes both theoretically and empirically and informs policymakers, regulators, and companies for promoting sustainability reporting to achieve sustainable development.
Keywords: 330; sustainability reporting; sustainable development; global competitive index; governance index